DETERGENT OF THE TOOTHPASTE AND ITS EFFECT ON ORAL CAVITY’S IMMUNITY - Коваленко, Поліна; Назаренко, Ірина; Громова, Тетяна (SWorldJournal, 2022)
The article considers 2 samples of one of the most common brands of toothpastes - "Colgate" and "Blend-a-med", their foaming ability, namely the content of detergent (surfactant). It was determined that sodium lauryl sulfate was used as a surfactant in b